Landasan Etis Kegiatan Ekonomi - Rachmat, Agus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
This article investigates the deeper foundation for the rapidly emerging and widespread consciousness in the business world on tbe nature and demand of the corporate social responsibility. Ethical norms and values should no longer be considered as externalistics, annoying additional costs and burdens to business interprices, but the very inner motivation for doing business at all, namely, to bring betterment to the world-wide human condition. That enduring noble al could only be accomplished if there is a comprehensive understanding on the kind of rationality that should permeate the so-called market society. In addition to the instrumental rationality that presently makes the market fluorish, we should also integrate what Max Weber called affective rationality and normative rationality.